Petunjuk Waktu Untuk Tuna Netra Dengan Output Suara - Aan Febriansyah; Muslim Fathillah; Nurdin Nurdin (Manutech : Jurnal Teknologi Manufaktur, 2018)
Nowaday time indicator as hour and calendar constitutes necessary for thing a lot of person to trip routines. In general, the clock and the calendar can only be seen by normal people. People with special needs, its example is blind will have difficulty in using the clock and the calendar Get bearing with that problem, therefore to help that blind is designed and made by time indicator tool with voice output. Generally, the tool's instructions when using RTC DS1307, is microcontroller ATmega16 and ISD 25 120. Information about hour, minute, date, month, and year obtained from DS1307 RTC is accessed using microcontroller ATmega16, then from the data when the information obtained is matched in the voice storage unit on ISD25120. As a results,will be obtained time information data such as voice. Besides, time setting, alarm, battery level indicator, and charge the battery with the sound as well is the tool is equipped permanently. Finally, this tool can help the blind people to be more independent in making it easier to tell the time in living day-to-day activities.